2014
DOI: 10.2147/ndt.s64219
|View full text |Cite
|
Sign up to set email alerts
|

Sensory disturbances, inhibitory deficits, and the P50 wave in schizophrenia

Abstract: Sensory gating disturbances in schizophrenia are often described as an inability to filter redundant sensory stimuli that typically manifest as inability to gate neuronal responses related to the P50 wave, characterizing a decreased ability of the brain to inhibit various responses to insignificant stimuli. It implicates various deficits of perceptual and attentional functions, and this inability to inhibit, or “gate”, irrelevant sensory inputs leads to sensory and information overload that also may result in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 126 publications
0
19
0
Order By: Relevance
“…A consistent observation in schizophrenia is that affected individuals are impaired in their ability to gate irrelevant sensory input ( Patterson et al, 2008 ). It has been proposed that sensory gating deficits lead to a sensory overload, which contributes to cognitive deficits in schizophrenia ( McGhie and Chapman, 1961 ; Shakow, 1963 ; Freedman et al, 1991 ; Bob et al, 2014 ). A commonly used experimental paradigm to study sensory gating is the auditory paired-stimulus paradigm, in which two identical stimuli are presented in close succession ( Adler et al, 1982 ; Bramon et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…A consistent observation in schizophrenia is that affected individuals are impaired in their ability to gate irrelevant sensory input ( Patterson et al, 2008 ). It has been proposed that sensory gating deficits lead to a sensory overload, which contributes to cognitive deficits in schizophrenia ( McGhie and Chapman, 1961 ; Shakow, 1963 ; Freedman et al, 1991 ; Bob et al, 2014 ). A commonly used experimental paradigm to study sensory gating is the auditory paired-stimulus paradigm, in which two identical stimuli are presented in close succession ( Adler et al, 1982 ; Bramon et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…They provide a noninvasive approach to study psychophysiological correlates of sensory and/or cognitive processes. Examples of these applications include the use of P50 to measure sensory gating (Olincy and Martin 2005; Vlcek et al 2014), N200 for assessing spatial attention (Woodman and Luck 2003), N250 as index of familiarity of face (Tanaka et al 2006) and P300 as a novelty or attention marker (Jeon and Polich 2001; Polich and Comerchero 2003). However, unlike those mentioned components, the N100 component, the negative deflection peak around 100 ms after the onset of stimulus, can be obtained from many if not all tasks in sensory domains.…”
Section: Introductionmentioning
confidence: 99%
“…Research has stated that primary cognitive disturbances in SCZ cause an inability to sufficiently filter and process sensory information, leading to disconnection of information and disrupted binding (McGhie and Chapman, 1961; Shakow, 1963; Freedman et al, 1991; Vlcek et al, 2014). Furthermore, electrophysiological studies have suggested that aberrant neural oscillations play a role for cognitive deficits in SCZ (Andreasen, 2000; Lee et al, 2003; Lisman, 2012; Pittman-Polletta et al, 2015; Senkowski and Gallinat, 2015; Uhlhaas and Singer, 2015; Keil et al, 2016).…”
Section: Introductionmentioning
confidence: 99%